2018
DOI: 10.1093/jas/sky003
|View full text |Cite
|
Sign up to set email alerts
|

Application of transmission infrared spectroscopy and partial least squares regression to predict immunoglobulin G concentration in dairy and beef cow colostrum

Abstract: The objective of this study was to explore the potential of transmission infrared (TIR) spectroscopy in combination with partial least squares regression (PLSR) for quantification of dairy and beef cow colostral immunoglobulin G (IgG) concentration and assessment of colostrum quality. A total of 430 colostrum samples were collected from dairy (n = 235) and beef (n = 195) cows and tested by a radial immunodiffusion (RID) assay and TIR spectroscopy. Colostral IgG concentrations obtained by the RID assay were lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…The relationship between VOCs and milk quality parameters was assessed using partial least squares (PLS), sometimes referred to as partial least squares regression. Partial least square analysis was developed in 1966 (Wold) and has been used in a variety of applications in dairy science and technology in the last decade (Macciotta et al 2006;Colombani et al 2012;Bonfatti et al 2017;Elsohaby et al 2018;Wu et al 2018). Partial least squares analysis bears a strong resemblance to principal component analysis (PCA) because it allows researchers to explore relationships among a set of variables.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between VOCs and milk quality parameters was assessed using partial least squares (PLS), sometimes referred to as partial least squares regression. Partial least square analysis was developed in 1966 (Wold) and has been used in a variety of applications in dairy science and technology in the last decade (Macciotta et al 2006;Colombani et al 2012;Bonfatti et al 2017;Elsohaby et al 2018;Wu et al 2018). Partial least squares analysis bears a strong resemblance to principal component analysis (PCA) because it allows researchers to explore relationships among a set of variables.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that the two Italian beef cows breed produce a colostrum with a higher IgG concentration than HF reared in Italy. IgG content of CHIA colostrum was higher than what has been reported in a French beef cattle breed (Vandeputte et al ., 2014) but lower than what was found in Irish (McGee et al ., 2005; Earley et al ., 2018) and Canadian beef herds (Homerosky et al ., 2017; Elsohaby et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…our measure of Holstein Friesian colostral immunoglobulin G concentration is comparable to what was reported by Quigley and colleagues (Quigley et al ., 2013) and slightly higher than data reported by Elsohaby et al . (2018).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 430 samples were analyzed and RID was the comparative method. The correlation measured with RID and TIR between the IgG concentration of two different colostrum sets was 0.84 and 0.96, respectively [ 43 ]. The correlations between RID and TIR concerning the IgG concentration are, in part, higher than the correlations measured between RID and the colostrometer [ 5 , 7 , 31 , 44 ] or the refractometer [ 11 , 20 , 34 , 45 ].…”
Section: Methods For Measuring the Immunoglobulin Concentration Of Colostrummentioning
confidence: 99%